Ozone biomonitoring using tobacco, Nicotiana tabacum "BelW3" - Edith Stabentheiner; Andrea Gross; Gerhard Soja; Dieter Grill (Acta Biologica Slovenica, 2003)
The ozone sensitive tobacco cultivar Be!W3 (Nicotiana tabacum L.) was used to monitor ozone pollution for one vegetation period (beginning of May till end of September) in Graz, a city of approximately 240 000 inhabitants in the south of Austria. The plants were exposed for 14 days in standardized shaded exposition racks. The insensitive tobacco cultivar BelB was used as a control. The leaf necroses characteristic for ozone damage were well correlated with ozone dose (AOT 40) with the exception of the first exposition period in May. The reliability of the evaluation of visible symptoms on tobacco leaves was confirmed by computer aided image analysis. It was possible to identify the spatial and temporal ozone distribution within a project area.